Parâmetros hematológicos, aspectos citoquímicos e ultraestruturais das células sanguíneas de três espécies de arraias (Chondrichthyes: Potamotrygonidae) do Médio Rio Negro, Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study aimed to present the information available of research on various aspects from freshwater stingrays. To obtain these results were achieved several bibliographic sources available. The results indicate that in the recent years there was a significant increase about the scientific knowledge of this group. Information on the diversity, and occurrence records are yet confusing, and have been made registration of new species, including even a new genus. Fishing is predominantly for use in aquarium, fishing negative result is the lack of existing environmental education. Wide variation was observed cytogenetic among all biological aspects investigated parasitology and food are the most studied. Aspects of reproductive biology are complex and there is a similarity to mammals than teleost fish. The information available so far in the literature are essential for this group of elasmobranchs occurring naturally only in South America, serving for future work practices in fisheries, aquaculture, ecology, genetics, evolution, management and mainly for conservation.
Keywords: Potamotrigonídeos; Arraia de água doce; Diversidade; Educação ambiental; Potamotrigonids; Diversity; CIÊNCIAS BIOLÓGICAS